Structural and functional characterization of hMEX‐3C Ring finger domain as an E3 ubiquitin ligase. (18th October 2018) - Moududee, Sayed Ala; Jiang, Yiyang; Gilbert, Nshogoza; Xie, Guodong; Xu, Zheng; Wu, Jihui; Gong, Qingguo; Tang, Yajun; Shi, Yunyu
Abstract: MEX‐3C, a novel RNA binding E3 ubiquitin ligases, contains two N‐terminal heterogeneous nuclear ribonucleoprotein K homology (KH) domains and C‐terminal Ring finger domain. Recent evidence has suggested that human MEX‐3C has a strong bondage with carcinogenesis and the MEX‐3C‐mediated ubiquitination of RIG‐I is essential for the antiviral innate immune response. Moreover, the Ring finger domain of MEX‐3C could regulate the degradation of HLA‐A2 (an MHC‐I allotype) mRNA with a novel mechanism. However, the structural basis for the ubiquitination catalyzed by hMEX‐3C Ring finger domain remains evasive. In this study, we solved the crystal structure of dimeric Ring finger domain of hMEX‐3C and compared it with the complex structure of MDM2/MDMX–UbcH5b–Ub. Our ubiquitination assay demonstrated that the Ring finger domain of hMEX‐3C acts as a ubiquitin E3 ligase in vitro, cooperating with specific E2 to mediate ubiquitination. Then, we identified several key residues in Ring finger domain of hMEX‐3C possibly involved in the interaction with E2–Ub conjugate and analyzed the E3 ligase activities of wild type and mutants at key sites. Additionally, zinc chelation experiments indicated that the intact structural stability is essential for the self‐ubiquitination activity of the Ring finger domain of hMEX‐3C. Taken together, our studies provided new insight into the mechanism of the Ring finger domain of hMEX‐3C that may play an important role in eliciting antiviral immune responses and therapeutic interventions.